Study on Gamification of the Subjects on Statistics: An Approach towards Designing an Escape Room - Sánchez-Cubo, F. (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
In recent years, education-understood as a mixture of methodologies- has suffered from a lack of innovation. Despite ICTs were implemented in many classrooms at all educational levels, something else was lacking. Consequently, gamification appeared as a solution to this issue. Thus, the objective of this piece of work is to design an educational Escape Room to be implemented in higher education and analysing the data extracted from an ad hoc questionnaire. Such questionnaire was fulfilled by the participants of the pilot experience after completing the game. Besides, ICTs are proposed as a way to deal with COVID-19 protocols and, additionally, lower monetary and time costs of implementation. The results show relevant correlations between different factors of the game, and general satisfaction is high. Therefore, notwithstanding the investment in time and effort, implementing an educational Escape Room seems useful for students.